Dose Dependent Effects of Fructose and Glucose on de novo Palmitate and Glycerol Synthesis in an Enterocyte Cell Model. Issue 1 (3rd December 2021) - Steenson, Simon; Shojaee‐Moradie, Fariba; Lovegrove, Julie A.; Umpleby, A. Margot; Jackson, Kim G.; Fielding, Barbara A.
Abstract : Scope: Fructose exacerbates post‐prandial hypertriacylglycerolaemia; perhaps partly due to increased enterocyte de novo lipogenesis (DNL). It is unknown whether this is concentration‐dependent or if fructose has a greater effect on lipid synthesis than glucose. Dose‐dependent effects of fructose and glucose on DNL and de novo triacylglycerol (TAG)‐glycerol synthesis are investigated in a Caco‐2 cell model. Methods and Results: Caco‐2 cells are treated for 96 h with 5, 25, or 50 mM fructose or glucose, or 12.5 mM fructose/12.5 mM glucose mix. DNL is measured following addition of [ 13 C2 ]‐acetate to apical media. Separately, [ 13 C6 ]‐fructose and [ 13 C6 ]‐glucose are used to measure DNL and de novo TAG‐glycerol synthesis. DNL from [ 13 C2 ]‐acetate is detected following all treatments, with greater amounts in intracellular than secreted (media) samples (all p < 0.05). DNL from [ 13 C6 ]‐fructose and [ 13 C6 ]‐glucose is also measurable. Intracellular synthesis is concentration‐dependent for both glucose ( p = 0.003) and fructose ( p = 0.034) tracers and is higher with 25 mM glucose than 25 mM fructose ( p = 0.025). DNL from fructose and glucose is <1%, but up to 70% of de novo TAG‐glycerol is synthesized from glucose or fructose. Conclusion: Fructose is not a major source of DNL in Caco‐2 cells but contributes substantially to de novo TAG‐glycerol synthesis. Abstract : This study treated intestinal Caco‐2 cells with three glucose and three fructose concentrations, and a glucose/fructose mixture, and traced the amount of de novo lipogenesis (DNL) and triacylglycerol (TAG)‐glycerol that was synthesised. Although glucose and fructose made a minor contribution to DNL (<1%), they provided the majority of glycerol used for TAG synthesis by Caco‐2 cells (30–70%).